I bandi liturgici nell'Egitto romano - Stroppa, Marco (Edizioni dell'Istituto Papirologico «G. Vitelli», 2017)
The calls for the appointment of the liturgical officers, that is, those who were obliged by the state to carry out public service duties, constitute a category of documents produced within the Roman administration of Egypt in the second and third centuries AD; these public notices were issued by the strategus, head of a region. It is a homogeneous group of Greek papyri - about twenty, including two unpublished texts - collected for the first time in this volume: a transcription is provided for each liturgical call, accompanied by the translation and a commentary. Through the comparative analysis of the texts, interesting data emerge to determine the typology of the documents and to reconstruct the development of some procedures of the liturgical system during the second and third centuries AD.